Synthesis of 5-Antipyriylazosalicylfluorone and its Colour Reaction with Molybdenum - Liu, Ying-Hong; Ma, Wei-Xing; Li, Yan-Hui; Liu, Juan (Asian Journal of Chemistry, 2010)
The synthesis of a new reagent, 5-antipyriylazosalicylfluorone was reported. The colour reaction between 5-antipyriylazosalicylfluorone and molybdenum(VI) was studied. In weak acid medium and in the presence of surfactant cetyltrimethylammonium bromide, Mo(VI) reacted with 5- antipyriylazosalicylfluorone to form a complex with the maximum absorption wavelength at 530 nm. Beer's law was obeyed in the range of 0-1.4 μg mL-1 for Mo(VI). The value of Mo(VI) content in food samples determined by this method was accordant with that measured by atomic absorption spectrophotometry. The relative standard deviation was 1.3-2.1 % for 7 replicate determinations. The recovery of the standard addition was 99.8-103.0 %.